Understanding social problems in Kuwait: implications for local community development - Almutairi, Nourah Saud Fwizan (Penerbit Universiti Kebangsaan Malaysia, 2025)
Local problems of countries around the world are increasing and are almost similar in terms of psychological disorders and problems. consequently, this study aimed to identify the nature of social problems in the State of Kuwait. Social problems in the State of Kuwait are increasing significantly, which affects local development. Therefore, the objectives of the study are to identify the social problems suffered by Kuwaiti society. The qualitative approach was used, where five female employees out of 11employees were interviewed, and the sample was withdrawn by the facilitated sample method. The results of the study showed that the nature of the problems suffered by Kuwaiti society, which is based on adolescents and children, are: movement disorders, academic achievement, depression, anxiety, as well as family problems, such as: Family disintegration. The purpose of this article is to describe the social problems in Kuwait comprising the understanding of their nature, causes and potential solutions. According to the study results, the study reached a number of recommendations, most notably working to spread and promote community development through social networking programmes, websites, radio and television programmes, and schools, as well as working to hold development and training workshops for community members in order to develop them, enhance their capabilities and development.